Learn more about

Refine search

Results (displaying matches 1-50 of 45894)  Next

Label Class Equation Sato-Tate \(\overline{\Q}\)-simple \(\GL_2\) Rank*
100000.a.200000.1 100000.a \(y^2 + y = 2x^5 + 5x^3 - 10x^2 + 5x - 1\) $\mathrm{USp}(4)$ 0
100010.a.400040.1 100010.a \(y^2 + (x^3 + 1)y = -x^6 + x^5 + 2x^4 + x^3 - 10x^2 + 2x + 5\) $\mathrm{USp}(4)$ 1
100017.a.300051.1 100017.a \(y^2 + (x^3 + x + 1)y = x^3 + x - 1\) $\mathrm{USp}(4)$ 0
100035.a.300105.1 100035.a \(y^2 + (x^3 + x + 1)y = -x^4 + x^3 - x^2 - 2x + 2\) $\mathrm{USp}(4)$ 1
100035.b.300105.1 100035.b \(y^2 + (x^3 + 1)y = x^5 - 3x^4 - 5x^3 + 11x^2 - 5\) $\mathrm{USp}(4)$ 1
100036.a.200072.1 100036.a \(y^2 + (x^3 + x^2 + 1)y = x^5 - 8x^3 - x^2 + 12x - 6\) $\mathrm{USp}(4)$ 2
100051.a.700357.1 100051.a \(y^2 + y = 7x^5 - 4x^4 + 2x^2 - x\) $\mathrm{USp}(4)$ 1
100059.a.100059.1 100059.a \(y^2 + xy = x^5 - x^3 - x\) $\mathrm{USp}(4)$ 1
100069.a.100069.1 100069.a \(y^2 + x^3y = x^5 + x^4 + 2x^3 + x - 1\) $\mathrm{USp}(4)$ 2
100076.a.200152.1 100076.a \(y^2 + (x^3 + x + 1)y = -6x^4 + 10x^3 - 2x^2\) $\mathrm{USp}(4)$ 2
100082.a.800656.1 100082.a \(y^2 + (x^3 + x)y = -7x^4 + 26x^2 - 29x + 9\) $\mathrm{USp}(4)$ 2
100089.a.100089.1 100089.a \(y^2 + (x^3 + x + 1)y = -x^5 + x^4 - 2x^2 + x\) $\mathrm{USp}(4)$ 2
100096.a.100096.1 100096.a \(y^2 = x^5 - 2x^4 - 3x^3 - 7x^2 - 7x - 2\) $\mathrm{USp}(4)$ 0
100096.b.100096.1 100096.b \(y^2 = x^5 - 9x^3 + 5x^2 + 21x - 20\) $\mathrm{USp}(4)$ 0
100096.c.100096.1 100096.c \(y^2 = x^5 - 9x^3 - 5x^2 + 21x + 20\) $\mathrm{USp}(4)$ 0
100109.a.100109.1 100109.a \(y^2 + y = x^5 + 2x^4 + 3x^3 + x^2 + x\) $\mathrm{USp}(4)$ 1
100121.a.100121.1 100121.a \(y^2 + (x^3 + x + 1)y = x^5 - 2x^2\) $\mathrm{USp}(4)$ 2
100121.b.700847.1 100121.b \(y^2 + (x^3 + x + 1)y = -x^4 + 3x^2 + 6x + 4\) $\mathrm{USp}(4)$ 2
100124.a.400496.1 100124.a \(y^2 + (x^2 + x)y = x^5 - 2x^4 + 2x^2 - 2x\) $\mathrm{USp}(4)$ 1
100128.a.801024.1 100128.a \(y^2 + (x^2 + 1)y = 4x^5 - x^4 - 13x^3 - 2x^2 + 7x - 2\) $\mathrm{USp}(4)$ 0
100130.a.200260.1 100130.a \(y^2 + (x^2 + x + 1)y = x^6 + 5x^5 + 6x^4 + x^2 + x\) $\mathrm{USp}(4)$ 2
100152.a.600912.1 100152.a \(y^2 + y = x^6 - 2x^5 - 6x^4 - 4x^3 + x\) $\mathrm{USp}(4)$ 2
100154.a.200308.1 100154.a \(y^2 + (x + 1)y = x^6 + x^5 + 2x^4 + 3x^3 + x^2\) $\mathrm{USp}(4)$ 2
100154.b.200308.1 100154.b \(y^2 + (x + 1)y = x^5 + x^3 - 5x^2 + 3x - 1\) $\mathrm{USp}(4)$ 0
100162.a.100162.1 100162.a \(y^2 + (x^3 + 1)y = x^5 - 2x^4 - 9x^3 + 8x^2 + 20x - 20\) $\mathrm{USp}(4)$ 2
100162.b.400648.1 100162.b \(y^2 + (x^2 + x)y = x^5 - 4x^4 + 4x^2 + 5x + 2\) $\mathrm{USp}(4)$ 1
100224.a.601344.1 100224.a \(y^2 = x^5 + 2x^4 + 4x^3 + 2x^2 + x - 1\) $\mathrm{USp}(4)$ 1
100224.b.601344.1 100224.b \(y^2 = x^5 + x^4 - 2x^3 + 4x^2 - 2x + 1\) $\mathrm{USp}(4)$ 1
100227.a.902043.1 100227.a \(y^2 + y = x^5 + x^4 + 23x^2 + 57x + 36\) $\mathrm{USp}(4)$ 1
100234.a.801872.1 100234.a \(y^2 + (x^3 + x)y = x^5 - x^4 - 5x^3 - x^2 + 5x - 3\) $\mathrm{USp}(4)$ 2
100240.a.400960.1 100240.a \(y^2 + x^3y = x^5 - x^4 - 5x^3 + 6x^2 + 10x - 15\) $\mathrm{USp}(4)$ 1
100261.a.100261.1 100261.a \(y^2 + (x + 1)y = x^5 - 16x^4 - x^3 + 7x^2 - 3x\) $\mathrm{USp}(4)$ 2
100261.b.100261.1 100261.b \(y^2 + xy = x^5 - x^4 + 3x^2 - 5x + 2\) $\mathrm{USp}(4)$ 1
100277.a.100277.1 100277.a \(y^2 + (x^3 + x^2 + 1)y = 2x^4 + 3x^3 - x^2 - x\) $\mathrm{USp}(4)$ 2
100277.b.100277.1 100277.b \(y^2 + y = x^5 + x^4 - 19x^3 - 11x^2 + 92x + 13\) $\mathrm{USp}(4)$ 0
100277.c.100277.1 100277.c \(y^2 + y = x^5 - 4x^4 + 4x^2 - 2x\) $\mathrm{USp}(4)$ 1
100278.a.200556.1 100278.a \(y^2 + x^2y = 2x^5 + 9x^4 + x^3 - 21x^2 + 15x - 3\) $\mathrm{USp}(4)$ 1
100283.a.100283.1 100283.a \(y^2 + (x^2 + 1)y = x^5 - x^4 - x^3 - x\) $\mathrm{USp}(4)$ 2
100293.a.902637.1 100293.a \(y^2 + (x^3 + x + 1)y = -x^6 + x^5 - 5x^4 + 3x^3 - 7x^2 + 2x - 2\) $\mathrm{USp}(4)$ 0
100309.a.100309.1 100309.a \(y^2 + xy = x^5 + 2x^3 - 3x^2 + x\) $\mathrm{USp}(4)$ 0
100312.a.200624.1 100312.a \(y^2 + (x^2 + 1)y = -x^6 - 2x^5 + x^4 + 3x^3 - x - 1\) $\mathrm{USp}(4)$ 0
100315.a.501575.1 100315.a \(y^2 + (x^3 + x + 1)y = 2x^5 + 3x^4 + x^3 + 2x^2 - 5x + 1\) $\mathrm{USp}(4)$ 2
100317.a.702219.1 100317.a \(y^2 + (x^2 + 1)y = x^5 - 10x^3 - 10x^2 + 28x + 38\) $\mathrm{USp}(4)$ 1
100325.a.100325.1 100325.a \(y^2 + x^2y = x^5 - 2x^4 + 4x^3 - 4x^2 + 3x - 1\) $\mathrm{USp}(4)$ 1
100325.b.100325.1 100325.b \(y^2 + (x^2 + x + 1)y = -x^5 + 3x^4 - 10x^2 + 2x + 8\) $\mathrm{USp}(4)$ 1
100341.a.100341.1 100341.a \(y^2 + y = x^5 - x^4 - 4x^3 - 5x^2 - 3x - 1\) $\mathrm{USp}(4)$ 1
100352.a.100352.1 100352.a \(y^2 = x^5 - x^4 + x^2 + x\) $N(G_{3,3})$ 0
100352.b.100352.1 100352.b \(y^2 = x^5 + x^4 - 5x^3 - 2x^2 + 4x - 1\) $\mathrm{USp}(4)$ 0
100352.c.100352.1 100352.c \(y^2 = x^5 - 9x^3 + 7x^2 + 14x - 14\) $\mathrm{USp}(4)$ 1
100352.d.100352.1 100352.d \(y^2 = x^5 - x^4 - 4x^3 + 3x^2 + 4x - 2\) $\mathrm{USp}(4)$ 1
Next
Download all search results for